Unemployment and Worker Participation in the Gig Economy: Evidence from an Online Labor Market - Huang, Ni; Burtch, Gordon; Hong, Yili; Pavlou, Paul A. (Information Systems Research, 2020)
The gig economy comprises a large portion of the workforce in today’s economy. The gig economy has low barriers to entry, enabling flexible work arrangements and allowing workers to engage in contingent employment, whenever, and in some cases, such as online labor markets, wherever, workers desire. And many of the workers seek and complete work via digital platforms. However, there is a lack of understanding into the participation in such platforms. The growth of the gig economy has been partly attributed to technological advancements that enable flexible work environments. In this study, we consider the role of an alternative driver, economic downturns, and associated financial stressors in the offline economy, for example, unemployment. Our analysis combines data from a leading online labor market and various archival sources such as the Bureau of Labor Statistics. We find local economic conditions significantly impact the intensive and extensive margins of labor supply in online labor markets. And such impacts are heterogeneous across different county characteristics. Given the prominence of the gig economy, we believe more research is needed to understand gig-economy participation. It is notable that policy makers recently started to look at related issues, proposing laws to protect the gig workers, such as the recent California Assembly Bill 5.